Practical utility of meropenem therapeutic drug monitoring: a systematic review of evidence for clinical application - Zhao, Yi-Chang; Liu, Jia-Yi; Li, Jia-Kai; Liu, Huai-Yuan; Sun, Zhi-Hua; Zhang, Bi-Kui; Yan, Miao (Frontiers in Pharmacology, 2025)
Background and purposeTherapeutic Drug Monitoring (TDM) is advocated to optimize antibiotic therapy, yet its efficacy remains debated. This systematic review and meta-analysis evaluates TDM’s impact on meropenem therapy, focusing on treatment efficacy, bacterial clearance, and changes in biomarkers (C-reactive protein (CRP) levels, procalcitonin (PCT) levels, white blood cell (WBC) count, neutrophil ratios).MethodsA systematic search was conducted across multiple databases, including PubMed, Embase, Web of Science, the Cochrane Library, and CNKI. Eligible studies comparing TDM with non-TDM approaches for meropenem were identified according to predefined inclusion and exclusion criteria. Pooled analyses were conducted using fixed-effects or random-effects models, selected based on the degree of heterogeneity among studies.ResultsA total of nine studies comprising 834 patients met the inclusion criteria and were included in the analysis. The study populations primarily consisted of adult and elderly patients with moderate to severe infections, including respiratory tract, urinary tract, and bloodstream infections. TDM significantly improved treatment efficacy (RR = 1.19; 95% CI: 1.10–1.28) and bacterial clearance rates (RR = 1.29; 95% CI: 1.12–1.48). CRP levels decreased significantly (mean difference = 14.91; 95% CI: 2.79–27.02), while changes in PCT, WBC, and neutrophil ratios were non-significant. Adverse reactions showed a non-significant reduction (RR = 0.65; 95% CI: 0.38–1.11). Low heterogeneity across studies supports the robustness of these findings.ConclusionTDM enhances treatment efficacy and bacterial clearance in meropenem therapy, but its impact on adverse reactions and certain biomarkers remains uncertain. Further research is needed to clarify TDM’s clinical utility and limitations.